The Therapeutic Landscape of Rheumatoid Arthritis: Current State and Future Directions - Shams, Shahin; Martinez, Joseph M.; Dawson, John R. D.; Flores, Juan; Gabriel, Marina; Garcia, Gustavo; Guevara, Amanda; Murray, Kaitlin; Pacifici, Noah; Vargas, Maxemiliano V.; Voelker, Taylor; Hell, Johannes W.; et al. (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a debilitating autoimmune disease with grave physical, emotional and socioeconomic consequences. Despite advances in targeted biologic and pharmacologic interventions that have recently come to market, many patients with RA continue to have inadequate response to therapies, or intolerable side effects, with resultant progression of their disease. In this review, we detail multiple biomolecular pathways involved in RA disease pathogenesis to elucidate and highlight pathways that have been therapeutic targets in managing this systemic autoimmune disease. Here we present an up-to-date accounting of both emerging and approved pharmacological treatments for RA, detailing their discovery, mechanisms of action, efficacy, and limitations. Finally, we turn to the emerging fields of bioengineering and cell therapy to illuminate possible future targeted therapeutic options that combine material and biological sciences for localized therapeutic action with the potential to greatly reduce side effects seen in systemically applied treatment modalities.